PENYULUHAN TENTANG PENDIDIKAN SEKS PADA ANAK USIA DINI UNTUK ORANG TUA - Dwi Khalisa Putri; Eliyana Lulianthy; Puja Usmiati Putri (Jurnal Inovasi dan Terapan Pengabdian Masyarakat, 2023)
Background Sexual abuse of children is a threat to the nation that can damage children, both physically, in their mindset, mentally and psychologically. According to data from the Ministry of Women and Child Protection (KPPA) in 2019, there were 1,500 reports of child sexual violence and abuse in Indonesia and the impact that could occur from this was physical, psychological damage and death. The aim is to determine parents' knowledge about sex education in early childhood. Method The targets in this activity are parents who have toddlers in the Posyandu working area of the Sungai Burung Village Health Center, Segedong District. The form of activity carried out is that first, at the posyandu, the mothers who attend are given a pretest questionnaire before being given health education counseling regarding sex education to children, then they are given a posttest questionnaire to assess the increase in knowledge among respondents. After the data processing was carried out, there were 33 respondents. The results of knowledge before counseling showed that the majority of respondents had good knowledge, namely 20 people (61%), while knowledge after counseling showed that the majority of respondents had good knowledge, namely 32 people (97%). The conclusion was that there was an increase in respondents' knowledge after being given counseling about early childhood sex education.